Correlation between the SERT binding densities in hypothalamus and amygdala in cloninger type 1 and 2 alcoholics - Storvik, Markus; Haukijärvi, Tuija; Tupala, Erkki; Tiihonen, Jari (Alcohol and alcoholism (Oxford), 2008)
Serotonin plays a role in the regulation of emotional states in amygdala which in turn affect the function of hypothalamus. The physiological effects of emotions are mediated to autonomic nervous system by the hypothalamus, also innervated by the serotonergic Raphe nuclei. Aims: We evaluated the putative alterations of the serotonin transporter (SERT) density in the paraventricular nucleus (PVN) of hypothalamus of Cloninger type 1 and 2 (early onset, anti-social) alcoholics and controls. Methods: The study was performed by human whole-hemisphere auto-radiography with [3H]citalopram. Results: Substantially sparser SERT density (−26%) with a moderate effect size (0.53) was observed in the hypothalamus of alcoholic subjects in relation to non-alcoholic comparison subjects, although the result failed to reach statistical significance. In type 2 alcoholics, there was a trend towards decreased SERT binding with large effect size (0.88), and no correlation between the SERT binding and the age at the time of death. There was a strong positive correlation between the SERT binding in amygdala and in PVN in type 2 alcoholics (P = 0.001), and negative correlation in type 1 alcoholics (P = 0.05), and no correlation in the control subjects. The difference between the groups was significant (χ 2 = 16.75, P = 0.0002). Conclusions: Taken together, these preliminary results support the hypothesis that the serotonergic regulation in the hypothalamus and amygdala are defected especially in type 2 alcoholics.